Assessment of the feed additive consisting of bentonite (1m558i) for all animal species for the renewal of its authorisation (EUBA aisbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the renewal of bentonite as a technological feed additive in the functional groups of binders, anticaking agents and substances for control of radionuclide contamination for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. There is no evidence that would lead the FEEDAP Panel to reconsider its previous conclusions. Thus, the Panel concluded that the additive remains safe for all animal species, consumers and the environment under the authorised conditions of use. Regarding user safety, the Panel concludes that bentonite is not irritant to the skin but is irritant to the eyes and should be considered a skin and respiratory sensitiser. Any exposure is considered a risk. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.